Implementation of the Hello Work Job Exchange Program in Reducing Unemployment in Pasuruan Regency - Silfiah, Rossa Ilma; Salsabilla, Salia Beby; Huda, Khoirul (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2026)
The Open Unemployment Rate (OUR) in Pasuruan Regency shows a significant figure, especially after the Covid-19 pandemic, peaking at 5.48% in 2023. One of the main causes of unemployment in this region is the mismatch between job seekers’ skills and industrial needs (skill mismatch). The Pasuruan Regency Government has implemented the Job Fair Program as a strategic effort to reduce unemployment rates, in line with Ministry of Manpower Regulation No. 18 of 2024 on Domestic Labor Placement. This study aims to analyze the implementation of the Job Fair Program in reducing unemployment in Pasuruan Regency, using George C. Edward III’s policy implementation model, which includes aspects of communication, resources, disposition, and bureaucratic structure. This study employs a qualitative method with a descriptive approach, through interviews, observations, and documentation. The findings shows that the Hello Work Job Exchange Program helped reduce unemployment in Pasuruan Regency, but there are issues with how the program is run. Problems include poor communication, lack of resources, and outdated vacancy information. Despite lower unemployment rates, participation in the program is decreasing, indicating indirect impact and limitations in effectiveness. The main challenge is the mismatch between job seekers' skills and industry needs, making successful placements difficult. The research results are expected to identify supporting and hindering factors in the program’s implementation and provide recommendations for optimizing the implementation of the Job Fair in Pasuruan Regency.